The Pin1-CaMKII-AMPA Receptor Axis Regulates Epileptic Susceptibility - Hou, Xiaojun (Cereb Cortex, 2021)
Pin1 is a unique isomerase that regulates protein conformation and function after phosphorylation. Pin1 aberration contributes to some neurological diseases, notably Alzheimer’s disease, but its role in epilepsy is not fully understood. We found that Pin1-deficient mice had significantly increased seizure susceptibility in multiple chemical inducing models and developed age-dependent spontaneous epilepsy. Electrophysiologically, Pin1 ablation enhanced excitatory synaptic transmission to prefrontal cortex (PFC) pyramidal neurons without affecting their intrinsic excitability. Biochemically, Pin1 ablation upregulated AMPA receptors and GluA1 phosphorylation by acting on phosphorylated CaMKII. Clinically, Pin1 was decreased significantly, whereas phosphorylated CaMKII and GluA1 were increased in the neocortex of patients with epilepsy. Moreover, Pin1 expression restoration in the PFC of Pin1-deficient mice using viral gene transfer significantly reduced phosphorylated CaMKII and GluA1 and effectively suppressed their seizure susceptibility. Thus, Pin1-CaMKII-AMPA receptors are a novel axis controlling epileptic susceptibility, highlighting attractive new therapeutic strategies.